Method for preparing three-color perovskite Micro-LED color conversion layer through laser processing

By preparing a three-color perovskite Micro-LED color conversion layer through laser processing, the problems of high production cost and low yield in Micro-LED technology are solved, high-resolution display and improved stability are achieved, production costs are reduced and yield is improved.

CN120813145APending Publication Date: 2025-10-17NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510910416.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Micro-LED technology has problems of high production cost and low yield rate in the production process, especially when tiny LEDs fall off during the mass transfer process, resulting in insufficient yield rate and difficulty in achieving high-resolution display.

Method used

Laser processing technology is used to prepare the three-color perovskite Micro-LED color conversion layer. By depositing LiF and Al films on the substrate and then performing laser processing to form a regional array, the perovskite solution is spin-coated on it, combined with Ag and LiF films, to achieve the preparation of the three-color color conversion layer, avoiding the mass transfer process.

Benefits of technology

It has achieved the manufacturing of high-resolution Micro-LED display devices, reduced production costs, improved yield, and extended device life. It also improved the stability of perovskite quantum dots through the LiF thin film protective layer, ensuring the uniformity of pixel luminescence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120813145A_ABST
    Figure CN120813145A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a three-color perovskite Micro-LED (Light Emitting Diode) color conversion layer by laser processing, which is characterized in that a LiF inorganic protective film and an Al metal color isolation film in a color conversion layer structure are treated by laser, and micro array processing with different resolutions is realized by adjusting laser processing parameters. And then spin coating is carried out on the metal color isolation film to form a perovskite film, and processing of the first layer of LED is completed. And subsequently, through repeated evaporation of a LiF inorganic protection film and an Ag metal color isolation film, laser processing and perovskite solution spin coating are matched, and manufacturing of a high-resolution Micro-LED color conversion layer device is achieved. And finally, evaporation of a LiF inorganic protective film is carried out on the top layer of the color conversion layer, and protection of the whole color conversion layer is achieved. According to the method, a large amount of complex procedures such as transferring are not needed, the machining cost is effectively saved, the yield of the LED array is remarkably improved, laser machining can be controlled through a computer, machining of different shapes is achieved, and preparation of complex patterns can be completed.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of perovskite materials, and particularly relates to a preparation method of a three-color perovskite Micro-LED color conversion layer prepared by laser processing. BACKGROUND

[0002] With the increasing demand of people for electronic display devices in recent years, the problem of how to effectively improve display precision has gradually

[0003] exposed, and Micro-LED technology has emerged as the times require under this background of demand and has become a hot research direction for improving display precision.

[0004] Compared with traditional LED display technology, Micro-LED technology forms LEDs with a small pitch through miniaturization and arraying, and the array size is controlled to be less than 100 μm, which is significantly smaller than the array size of 300 μm to 1000 μm of traditional LED technology, so that the number of pixel points is effectively increased, and the display precision is improved.

[0005]

[0006] Compared with various display technologies (LCD, OLED, QLED) existing on the market, Micro-LED has certain advantages in service life, photoelectric performance, contrast brightness and the like. Especially with the continuous upgrading of near-eye technology, the demand gap for high-resolution devices is also expanding, so its application prospect is also favored by the public.

[0007]

[0008] Micro-LED technology is still in its infancy, and there is still a lot of room for improvement in performance, which is undoubtedly the direction of the next generation of display technology. Perovskite materials have been considered as very promising semiconductor materials in recent years because of their unique performance and excellent optical properties.

[0009] Perovskite as a luminescent material has a high degree of adaptation with Micro-LED, so researchers in the display field at home and abroad have tried to combine the two. However, there are two big problems in the actual production process of Micro-LED, that is, high production cost and low yield.

[0010]

[0011] The main core part of this technology is the mass transfer of micro-LED, and the production cost is mostly concentrated in the mass transfer. The main core part of this technology is the mass transfer of micro-LED, and the production cost is mostly concentrated in the mass transfer.

[0012]

[0013]

[0014] ​​​​​In the process of mass transfer, the falling of part of the micro-LEDs often causes insufficient yield, and a secondary supplement process is needed

[0015] The production cost is increased. Therefore, many researchers in this field at home and abroad are trying to solve the two problems, including the method of using a color conversion layer. SUMMARY

[0016] The purpose of the present application is to provide a method for preparing a three-color perovskite Micro-LED color conversion layer without mass transfer by combining existing laser technology. The method completes the morphology processing of the microarray by laser processing of the sample after evaporation, prepares a perovskite film on the processed surface, protects the perovskite film with LiF, and realizes the effect of color crosstalk isolation with Al and Ag, finally realizes the preparation of a three-color color conversion layer, and realizes the purpose of high-resolution Micro-LED technology without mass transfer.

[0017] In the first aspect, the present application provides a method for preparing a three-color perovskite Micro-LED color conversion layer by laser processing, comprising the following steps:

[0018] Step 1: depositing a LiF protective film and an Al color separation film on a clean glass substrate treated by ultraviolet cleaning in sequence;

[0019] Step 2: laser processing the deposited LiF film and Al film to form a regional array;

[0020] Step 3: spin coating a red perovskite solution on the regional array of step 2 on a film applicator to form a red perovskite film;

[0021] Step 4: depositing an Ag film and a LiF film on the red perovskite film in sequence;

[0022] Step 5: laser processing the deposited Ag film and LiF film of step 4 to form a regional array;

[0023] Step 6: spin coating a green perovskite solution on the regional array of step 5 on a film applicator to form a green perovskite film;

[0024] Step 7: depositing an Ag film and a LiF film on the green perovskite film in sequence;

[0025] Step 8: laser processing the deposited Ag film and LiF film of step 7 to form a regional array;

[0026] Step 9: spin coating a blue perovskite solution on the regional array of step 8 on a film applicator to form a blue perovskite film;

[0027] Step 10: depositing a LiF film on the blue perovskite film.

[0028] Preferably, in step 1, the LiF film and the Al film are sequentially deposited on the clean glass substrate subjected to ultraviolet cleaning treatment in a vacuum evaporation machine, the thickness of the LiF film is 100 nm, and the thickness of the Al film is 100 nm.

[0029] Preferably, in steps 3, 6 and 9, the laser is a 532 nm pulsed laser, the pulse energy is 15-20 muJ, the processing speed is 10-30 mm / s, and the processing frequency is 80 Hz. 2 The perovskite solution is spin-coated on the substrate at a rate of 2500 rpm for 45 s.

[0030] Preferably, the red perovskite is CsPbBrI2, the green perovskite is CsPbBr3, and the blue perovskite is CsPbClBr2, and the solvent of each perovskite solution is n-hexane, and the concentration of each solution is 0.2 mmol / L.

[0031] Preferably, in steps 4 and 7, the LiF film has a thickness of 60 nm, and the Ag film has a thickness of 60 nm.

[0032] Preferably, in steps 2, 5 and 8, the laser is a 532 nm pulsed laser, the pulse energy is 15-20 muJ, the processing speed is 10-30 mm / s, and the processing frequency is 80 Hz.

[0033] Preferably, in step 10, the thickness of the LiF film is 100 nm.

[0034] Compared with the prior art, the present application has the following advantages:

[0035] 1. The present application realizes high-resolution Micro-LED without the need for massive transfer, has low requirements for equipment, and has low production process cost.

[0036] 2. The present application can adjust the surface morphology of laser action by adjusting the process light path, and can adjust the array point morphology according to requirements.

[0037] 3. The present application can control laser parameters through adjustment programs to complete processing of different size arrays and realize manufacturing of different resolution Micro-LED display devices.

[0038] 4. The present application improves the stability of perovskite quantum dots and prolongs the service life of the device by adding a LiF film as a packaging protective layer on the perovskite quantum dot film.

[0039] 5. The present application uses Al film and Ag film as color separation layers to ensure the uniformity of pixel light emission, making the device have more excellent light emission performance.

[0040] 6. The present application provides an effective method for the stable existence of perovskite thin films in display devices.

[0041] 7. The present application has certain expandability in materials, not only suitable for perovskite materials, but also has certain applicability for light-emitting materials. BRIEF DESCRIPTION OF DRAWINGS

[0042] Figure 1 The flow chart of 532nm pulse laser processing for the Micro-LED color conversion layer.

[0043] Figure 2 The internal structure diagram of the processed color conversion layer.

[0044] Figure 3 (a) in the details of the single array prepared by using CsPbBrI2 red perovskite solution, (b) is the details of the single array prepared by using CsPbClBr2 blue perovskite solution, (c) is the details of the single array prepared by using CsPbBr3 green perovskite solution

[0045] Figure (d) is the array details formed by laser processing.

[0046] Figure 4 (a) three-color perovskite array (b) three-color perovskite pattern.

[0047] Figure 5 The luminescence intensity change of the packaged perovskite quantum dots.

[0048] Figure 6 The quantum dot fluorescence intensity distribution of the prepared array device. DETAILED DESCRIPTION

[0049] The present application will be further illustrated below in combination with specific test examples, and it should be understood that these examples are only used to illustrate the present application and not used to limit the

[0050] The scope of the present application, after reading the present application, the various equivalent forms of the present application are modified by those skilled in the art, and fall within the scope of the present application.

[0051] The scope defined by the claims attached to the application.

[0052] The present application proposes a technical method for realizing three-color perovskite Micro-LED based on laser processing technology. The color conversion layer structure is processed by using laser, and different sizes of arrays are realized by adjusting the laser processing parameters.

[0053] The LiF inorganic protective film and Al metal color separation film in the color conversion layer structure are processed, and different sizes of arrays are realized by adjusting the laser processing parameters.

[0054] The micro-array processing of high resolution is then performed. Then, a perovskite film is formed by spin coating on the metal color barrier film, completing the processing of the first layer of LED.

[0055] By repeatedly evaporating LiF inorganic protective film and Ag metal color isolation film, combined with laser processing and perovskite solution spin coating, high resolution

[0056] Finally, the LiF inorganic protective film is evaporated on the top layer of the color conversion layer to achieve

[0057] The protection of the overall color conversion layer. This method does not require complex processes such as massive transfer, effectively saving processing costs and significantly improving LED

[0058] The yield rate of the array can be improved, and laser processing can be controlled by computer to achieve processing of different morphologies and complete the preparation of complex patterns. It has huge development potential in Micro-LED display technology.

[0059] Example 1

[0060] Laser treatment of LiF film and Al / Ag metal layer and perovskite layer in color conversion layer structure according to preparation process and equipment

[0061] Spin coating. The specific process is mainly divided into four steps, and its main experimental equipment is as follows: Figure 1 The laser is a 532nm pulsed laser, the focusing objective lens magnification is ×50, the red perovskite material is CsPbBrI2, and the ultrasonic cleaning solvent is acetone solution and deionized water.

[0062] The specific test steps are as follows:

[0063] Step 1: In a vacuum evaporation machine, LiF and Al are deposited sequentially on a clean surface that has been cleaned by ultraviolet light by vacuum evaporation.

[0064] On a glass substrate (1cm*1cm), a LiF protective film and an Al color barrier film are formed. The steps are as follows:

[0065] Step 1.1: Place the glass substrate in a beaker and add acetone solution to the beaker to submerge the glass substrate to be cleaned.

[0066] Turn on the ultrasonic cleaning machine, set the power, and perform ultrasonic cleaning on the glass substrate for 20 minutes.

[0067] Step 1.2: Place the glass substrate cleaned in step 1.1 into a UV-ozone cleaning machine for further cleaning for 20 minutes.

[0068] Step 1.3: The cleaned glass substrate in step 1.2 is transferred into the evaporation chamber under vacuum environment, and the glass substrate is placed on the evaporation template to prepare the LiF protective film and Al color barrier film.

[0069] Step 1.4: Close the evaporation chamber door, open the evaporation mechanical pump, and vacuumize the evaporation chamber environment. When the chamber pressure is below 10 Pa, open the molecular pump for continuous vacuumization until the chamber environment pressure is below 5*10 -4 Pa.

[0070] Step 1.5: Set the evaporation process parameters. The evaporation speed can be controlled by adjusting the evaporation current and evaporation voltage to ensure that the evaporation speed is below 0.1 nm / s until the thickness of the LiF protective film and Al color barrier film reaches 100 nm.

[0071] Step 1.6: After the evaporation of the LiF protective film and Al color barrier film is completed, the chamber is vented, and the chamber door is opened after the pressure is the same as that in the glove box to take out the completed sample.

[0072] Step 2: Laser processing is performed on the deposited Al layer and LiF layer to form a regional array, as shown in (d) of FIG. 1. Figure 3

[0073] The steps are as follows:

[0074] Step 2.1: Place the completed sample on the processing platform, and use the processing platform lifting control software in the computer to adjust the sample position to the laser focal length position.

[0075] Step 2.2: Adjust the laser processing parameters according to the required array lateral size, including laser motion speed, laser pulse frequency, laser attenuation ratio, etc.

[0076] Step 2.3: Adjust the processing pattern size using the drawing software in the computer according to the required array longitudinal size.

[0077] Step 2.4: Select the processing part of the pattern drawn by the drawing software, adjust the laser energy to 15 μJ, the processing speed to 20 mm / s, and the processing frequency to 80 Hz.

[0078] Step 3: Spin-coat the red perovskite solution on the regional array on the spin coater to form a red perovskite film. The steps are as follows:

[0079] ​Step 3.1: Transfer the sample into the spin coater for red perovskite film preparation. Set the spin coater parameters: speed 2500 rpm, time 45 s. Use a pipette to quickly drop 40 μL of prepared CsPbBrI2 solution onto the Al color separation film, and turn on the spin button to form a film.

[0080] Step 3.2: Place the spin-coated sample in a light-proof place for 1 hour of air drying.

[0081] Step 4: Use vacuum evaporation to deposit LiF on the red perovskite film. Details are as follows:

[0082] Step 4.1: Transfer the air-dried sample into the evaporation cabin in a vacuum environment, and place the sample on the evaporation template to prepare for LiF protection film evaporation.

[0083] Step 4.2: Close the evaporation cabin door, turn on the evaporation mechanical pump, and perform vacuum treatment on the evaporation cabin environment. When the cabin pressure reaches below 10 Pa, turn on the molecular pump for continuous vacuum treatment until the cabin environment pressure is below 5*10 -4 Pa.

[0084] Step 4.3: Set the evaporation process parameters. Adjust the evaporation current and evaporation voltage to control the evaporation speed, ensuring that the evaporation speed is below 0.1 nm / s until the LiF protection film thickness reaches 60 nm.

[0085] Step 4.4: After completing the LiF protection film evaporation, release the cabin, open the cabin door when the cabin pressure is the same as the glove box pressure, and take out the evaporation completed sample. As shown in (a) of Figure 3 , the red pixel array emits light uniformly and has high brightness, with a pixel spacing of about 40 μm.

[0086] Place the sample in a water-oxygen environment for different lengths of time for light spectrum analysis. The results are shown in Figure 5 . Within 8 days, the red perovskite quantum protected by the LiF film can maintain more than 90% of the light intensity, and after 20 days, it can still maintain about 55% of the light intensity.

[0087] Example 2

[0088] The specific steps are the same as in Example 1, except that the red perovskite CsPbBrI2 is replaced by the blue perovskite CsPbClBr2. The results are shown in (b) of Figure 3 , the blue pixel array emits light uniformly and has high brightness, with a pixel spacing of about 40 μm.

[0089] Place the sample in a water-oxygen environment for different lengths of time for light spectrum analysis. The results are shown in Figure 5As shown in FIG. 8, the blue perovskite quantum dots can maintain more than 90% of the luminous intensity within 8 days, and more than 80% of the luminous intensity within 20 days.

[0090] Example 3

[0091] The specific steps are the same as those in Example 1, except that the red perovskite CsPbBrI2 is replaced by the green perovskite CsPbBr3, and the results are as shown in FIG. 6. Figure 3 As shown in (c) of FIG. 6, the green pixel array emits light uniformly and has high brightness, and the pixel spacing is about 40 pm.

[0092] The sample is placed in a water-oxygen environment for a long time of luminescence spectrum analysis, and the results are as shown in FIG. 8. Figure 5 As shown in FIG. 8, the green perovskite quantum dots can maintain more than 90% of the luminous intensity within 8 days, and more than 80% of the luminous intensity within 20 days.

[0093] Example 4

[0094] According to the preparation process and device, laser treatment of the LiF thin film and the Al / Ag metal layer and spin coating of the perovskite layer in the color conversion layer structure are performed. The specific process mainly includes ten steps, and the main experimental device is as shown in FIG. 5. Figure 1 Among them, the laser is a 532 nm pulsed laser, the focusing objective lens magnification is x50, the red, green and blue perovskite is CsPbBrI2, CsPbBr3 and CsPbClBr2 respectively, and the ultrasonic cleaning solvent is acetone solution and deionized water.

[0095] The specific test steps are as follows:

[0096] Step 1: in a vacuum evaporation machine, LiF and Al are sequentially deposited on a clean glass substrate (1 cm*1 cm) treated by ultraviolet cleaning to form a LiF protective film and an Al color separation film; the steps are as follows:

[0097] Step 1.1: place the glass substrate in a beaker, add acetone solution in the beaker to immerse the glass substrate to be cleaned, turn on the ultrasonic cleaning machine, set the power, and ultrasonically clean the glass substrate for 20 minutes.

[0098] Step 1.2: further clean the glass substrate cleaned in step 1.1 in an ultraviolet ozone cleaning machine for 20 minutes.

[0099] Step 1.3: transfer the cleaned glass substrate in step 1.2 to the evaporation cabin in a vacuum environment, and then place the glass substrate on the evaporation template to prepare the evaporation of the LiF protective film and the Al color separation film.

[0100] Step 1.4: Close the evaporation chamber door, open the evaporation mechanical pump, and vacuumize the evaporation chamber environment. When the chamber pressure reaches below 10 Pa, open the molecular pump for further vacuumization until the chamber pressure is below 5*10 -4 Pa.

[0101] Step 1.5: Set the evaporation process parameters. Adjust the evaporation current and voltage to control the evaporation speed, ensuring that the evaporation speed is below 0.1 nm / s until the LiF protective film and Al color barrier film thickness reach 100 nm.

[0102] Step 1.6: After completing the evaporation of the LiF protective film and Al color barrier film, release the gas in the chamber. When the pressure is the same as the pressure in the glove box, open the chamber door and take out the sample after evaporation.

[0103] Step 2: Laser processing of the deposited Al film and LiF film to form a regional array, as shown in d in Figure 3 .

[0104] The steps are as follows:

[0105] Step 2.1: Place the sample after evaporation on the processing platform. Use the processing platform lifting control software in the computer to adjust the sample position to the laser focal length position.

[0106] Step 2.2: Adjust the laser processing parameters according to the required array transverse size. The laser processing parameters include: laser motion speed, laser pulse frequency, laser attenuation ratio, etc.

[0107] Step 2.3: Adjust the processing pattern size using the drawing software in the computer according to the required array longitudinal size.

[0108] Step 2.4: Select the processing part of the pattern drawn by the drawing software, adjust the laser energy to 15 μJ, the processing speed to 30 mm / s, and the processing frequency to 80 Hz for laser processing.

[0109] Step 3: Spin-coat the red perovskite solution on the Al color barrier film on the spin coater to form a red perovskite film. The steps are as follows:

[0110] Step 3.1: Transfer the sample to the spin coater to prepare the red perovskite film. Set the spin coater parameters: speed 2500 rpm, time 45 s. Use a pipette to quickly drop 40 μL of prepared CsPbBrI2 solution on the Al color barrier film, and turn on the spin-coating button to form a film.

[0111] Step 3.2: Place the spin-coated sample in a dark place to dry for 1 hour.

[0112] Step 4: Vacuum evaporation method is used to deposit Ag and LiF on the red perovskite film. The specific process is as follows:

[0113] Step 4.1: After air-drying, the sample is transferred to the evaporation cabin in a vacuum environment, and then placed on the evaporation template to prepare the Ag color barrier film and LiF protective film.

[0114] Step 4.2: Close the evaporation cabin door, open the evaporation mechanical pump, and perform vacuum treatment on the evaporation cabin environment. When the cabin pressure reaches below 10 Pa, open the molecular pump for further vacuum treatment until the cabin environment pressure is below 5*10 -4 Pa.

[0115] Step 4.3: Set the evaporation process parameters. Adjust the evaporation current and voltage to control the evaporation speed, ensuring that the evaporation speed is below 0.1 nm / s, until the thickness of the LiF protective film and Ag color barrier film reaches 60 nm.

[0116] Step 4.4: After completing the evaporation of the LiF protective film and Al color barrier film, release the pressure in the cabin. When the cabin pressure is the same as the glove box pressure, open the cabin door and remove the completed sample.

[0117] Step 5: Laser processing is performed on the deposited Ag film and LiF film to form an array of regions. The specific process is as follows:

[0118] Step 5.1: Place the sample at the position of the last laser processing. Adjust the laser processing parameters according to the required array size.

[0119] Step 5.2: Adjust the processing pattern size using the drawing software in the computer according to the required array size.

[0120] Step 5.3: Select the processing part of the pattern drawn by the drawing software, adjust the laser energy to 15 μJ, set the processing speed to 30 mm / s, and perform laser processing at a processing frequency of 80 Hz.

[0121] Step 6: On the spin coater, spin-coat the green perovskite solution on the LiF protective film to form a green perovskite film. The specific process is as follows:

[0122] Step 6.1: Transfer the sample to the spin coater to prepare the green perovskite film. Set the spin coater parameters: speed 2500 rpm, time 45 s. Use a pipette to quickly drop 40 μL of prepared CsPbBr3 solution on the LiF protective film, and turn on the spin coating button to form a film.

[0123] Step 6.2: Place the spin-coated sample in a light-proof place to dry for 1 hour.

[0124] Step 7: Use vacuum evaporation method to deposit Ag and LiF on the green perovskite film. Specifically as follows:

[0125] Step 7.1: Transfer the dried sample into the evaporation cabin in a vacuum environment, and place the sample on the evaporation template to prepare for the evaporation of LiF protective film and Ag color separation film.

[0126] Step 7.2: Close the evaporation cabin door, open the evaporation mechanical pump, and perform vacuum treatment on the evaporation cabin environment. When the cabin pressure reaches below 10 Pa, open the molecular pump for further vacuum treatment until the cabin environment pressure is below 5*10 -4 Pa.

[0127] Step 7.3: Set the evaporation process parameters. Adjust the evaporation current and evaporation voltage to control the evaporation speed, ensuring that the evaporation speed is below 0.1 nm / s, until the thickness of the LiF protective film and Ag color separation film reaches 60 nm.

[0128] Step 7.4: After completing the evaporation of the LiF protective film and Al color separation film, release the pressure in the cabin. When the cabin pressure is the same as the glove box pressure, open the cabin door and take out the completed sample.

[0129] Step 8: Perform laser processing on the deposited Ag film and LiF film to form a regional array. Specifically as follows:

[0130] Step 8.1: Place the sample at the position of the last laser processing, and adjust the laser processing parameters according to the required array horizontal size.

[0131] Step 8.2: Adjust the processing pattern size using the drawing software in the computer according to the required array vertical size.

[0132] Step 8.3: Select the processing part of the pattern drawn by the drawing software, adjust the laser energy to 15 μJ, set the processing speed to 30 mm / s, and perform laser processing at a processing frequency of 80 Hz.

[0133] Step 9: On the spin coater, spin-coat the blue perovskite solution on the LiF protective film to form a blue perovskite film. Specifically as follows:

[0134] Step 9.1: Transfer the sample to the spin coater to prepare the blue perovskite film. Set the spin coater parameters: speed 2500 rpm, time 45 s. Use a pipette to quickly drop 40 μL of prepared CsPbClBr2 solution on the LiF protective film, and turn on the spin coating button to form a film.

[0135] Step 9.2: The sample after spin coating was placed in a dark place to dry for 1 hour.

[0136] Step 10: The sample was deposited with LiF on the perovskite film by vacuum evaporation. Specifically as follows:

[0137] Step 10.1: The dried sample was transferred to the evaporation cabin in a vacuum environment, and the sample was placed on the evaporation template to prepare for the evaporation of the LiF protective film.

[0138] Step 10.2: Close the evaporation cabin door, open the evaporation mechanical pump, and vacuumize the evaporation cabin environment. When the cabin pressure is below 10 Pa, open the molecular pump for further vacuumization until the cabin environment pressure is below 5*10 -4 Pa.

[0139] Step 10.3: Set the evaporation process parameters. The evaporation speed can be controlled by adjusting the evaporation current and evaporation voltage to ensure that the evaporation speed is below 0.1 nm / s until the LiF protective film thickness reaches 100 nm.

[0140] Step 10.4: After completing the evaporation of the LiF protective film, the cabin was vented, and the cabin door was opened after the pressure was the same as the glove box pressure. The sample after evaporation was taken out, and the results are shown in (a) of Figure 4 .

[0141] The sample was analyzed for fluorescence intensity, and the results are shown in Figure 6 . The pixel surrounding boundary is clear and no other fluorescence distribution appears, indicating that the structure effectively avoids the crosstalk problem between different color pixels. At the same time, the pixel point light emission shows a highly similar smooth column, indicating that each pixel point light emission is similar, with good light emission uniformity.

[0142] Example 5

[0143] The specific steps are the same as in Example 4. The difference is that the laser processing parameters in steps 2.4, 5.3, and 8.3 are adjusted. The laser energy is adjusted to 20 μJ, the laser processing frequency is 80 Hz, and the processing speed is 10 mm / s. The results are shown in (b) of Figure 4 .

Claims

1. A method for preparing a three-color perovskite Micro-LED color conversion layer by laser processing, characterized in that: The following steps are involved: Step 1: On a clean glass substrate treated with UV light, a LiF protective film and an Al color barrier film are sequentially deposited; Step 2: Laser processing the deposited LiF film and Al film to form a regional array; Step 3: On a spin coater, spin-coat the red perovskite solution onto the area array of step 2 to form a red perovskite film; Step 4: Depositing an Ag thin film and a LiF thin film sequentially on the red perovskite film; Step 5: Laser processing the Ag film and LiF film deposited in step 4 to form a regional array; Step 6: Spin-coat the green perovskite solution onto the area array in step 5 on a spin coater to form a green perovskite film; Step 7: Depositing an Ag thin film and a LiF thin film sequentially on the green perovskite film; Step 8: Laser processing the Ag film and LiF film deposited in step 7 to form a regional array; Step 9: Spin-coat the blue perovskite solution onto the area array in step 8 on a spin coater to form a blue perovskite film; Step 10: Depositing a LiF thin film on the blue perovskite film.

2. The method according to claim 1, wherein In step 1, a LiF film and an Al film are sequentially deposited by vacuum evaporation on a clean glass substrate that has been cleaned by ultraviolet light in a vacuum evaporation machine. The thickness of the LiF film is 100 nm, and the thickness of the Al film is 100 nm.

3. The method according to claim 1, wherein In steps 3, 6, and 9, every 1 cm 2 40~60μL of perovskite solution were spin-coated on the substrate, with a spin-coating rate of 2500 rpm and a spin-coating time of 45s.

4. The method according to claim 1, wherein The red perovskite is CsPbBrI2, the green perovskite is CsPbBr3, and the blue perovskite is CsPbClBr2. The solvent of each perovskite solution is n-hexane, and the solution concentration is 0.2 mmol / L.

5. The method according to claim 1, wherein In steps 4 and 7, vacuum evaporation was used, and the thickness of the LiF film was 60 nm, and the thickness of the Ag film was 60 nm.

6. The method according to claim 1, wherein In steps 2, 5, and 8, the laser used is a 532 nm pulsed laser with a pulse energy of 15-20 μJ, a processing speed of 10-30 mm / s, and a processing frequency of 80 Hz.

7. The method according to claim 1, wherein In step 10, the thickness of the LiF film is 100 nm.